Implementation of Aptitude Treatment Interaction (ATI) in Nahwu Learning: Identification of Student Ability Characteristics - Hikmah Maulani; Maman Abdurrahman; Nalahuddin Saleh; Ahmad Faqih; Faiz Dzul Fahmi Hamdan (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
Aptitude Treatment Interaction (ATI) is used as a learning method that treats differences in student abilities; this is considered appropriate for Nahwu learning. The purpose of this study is to elaborate on Nahwu's learning activities using Aptitude Treatment Interaction (ATI) through the involvement of lecturers and students. This study uses a qualitative approach; the participants are non-Arabic speaking Nahwu students in Indonesia, totaling 40 students. Data collection techniques are using observation, structured interviews, and using questionnaires. The results showed that there were implications for the use of Aptitude Treatment Interaction (ATI) in learning motivation, as indicated by an increase in scores on the evaluation of students' Nahwu understanding abilities and perceptions that showed a good assessment of this method. The recommendation of this research is the preparation of teaching materials based on Aptitude Treatment Interaction (ATI) for Nahwu learning that can be done at universities in Indonesia.